The Implications of China’s Regional Military Power Projections: Challenges for India’s Military Strategy - Amin, Khoirul (Global Local Interactions: Journal of International Relations, 2019)
The economic revival became the main locomotive for China to continue its modernization and military strength building program. As a representation of the 21st century's global power, China has proven a stronger and more aggressive revival. Aggressiveness in building military strength in quality and quantity has influenced the security order in the Asian region and encouraged him to be more assertive in dealing with security issues involving his region. India is one of the most threatened countries. The spread of military power along with provocative actions of China in the border region with India, the intensification of the development of maritime facilities and infrastructure in the Indian Ocean region, as well as the superiority of Chinese combat power over India are some of the strong basic reasons for India to make China a major threat to the security of its territory. With limited strength and combat capabilities under China, India responded to China's military threat by increasing its defense power. Defensive military strategy became the most rational choice and more profitable for India in order to reduce the aggressiveness and threat of the Chinese military power.Keywords : China’s military power; Chinese military threat; India’s military strategy